Planning for Publication Development on Room Sales in Sevenz Apartment - Felinda, Viona; Lubis, Arina Luthfini (Media Wisata, 2024)
The apartment business presents a lucrative opportunity when employing effective marketing strategies, including social media publications which can enhance brand awareness and customer satisfaction. In Batam, an international industrial hub, the demand for accommodation is on the rise, and entrepreneurs such as the owners of Sevenz Apartments are capitalizing on this opportunity by developing daily and monthly rental businesses. However, there is a need for additional strategies to address the seasonal imbalance in occupancy rates. Therefore, the researcher developed publications for Sevenz Apartments. A descriptive design was employed in this study. Given the qualitative nature of the data, interviews were conducted to collect firsthand data from informants regarding publications in the marketing of Sevenz Apartments. Based on the interview results, a website was developed as the primary promotional platform providing comprehensive information about facilities, prices, and promotions. This website is expected to increase visibility and room sales by expanding the audience reach and utilizing social media and content marketing.